Parental Report of Self and Child Worry During Acute Pain: A Critical Factor in Determining Parental Pain Judgment. Issue 8 (August 2019) - Mamedova, Khuraman; Pillai Riddell, Rebecca R.; DiLorenzo, Miranda G.; Flora, David B.; Garfield, Hartley; Greenberg, Saul
Abstract : Objective: The objective of this study was to determine which variables predict parental postvaccination pain ratings. It was hypothesized that after child behavior, parental sensitivity, and parental reports of worry would be the strongest predictors. Methods: Data for 215 parent-child dyads were analyzed from a longitudinal cohort at the preschool (4 to 5 y of age) vaccination. Preschoolers' pain behaviors 15 seconds, 1 minute 15 seconds, and 2 minutes 15 seconds after the painful immunization were observed and rated. Parental sensitivity, as well as parental own worry and their assessment of their child's worry, were assessed before and after the needle. Three regression models were used to determine the impact of these variables on parental pain assessment. Results: Preschoolers' pain behaviors moderately accounted for variance in parental pain judgment ( R 2 =0.23 to 0.28). Parental sensitivity was not a significant unique predictor of parental pain rating at the preschool age. Parental assessment of their own worry and worry about their preschoolers after the needle were critical contributors to parental pain judgment. Post hoc analyses suggest that parents who report low child worry, are more congruent with their child during regulatory phases postvaccination. However, both parents with high and low self-worry had more congruent pain ratings with child pain behavior scores during the reactivity phase. Discussion: The study suggests that the majority of variance in parent pain ratings was not predominantly based on preschoolers' pain behaviors. Parental worry levels and their assessment of their child's worry were also significant predictors. Clinical implications are discussed.